Bullseye [compact disc, unabridged] - Patterson, James, 1947-; Ledwidge, Michael (Patterson, James, 1947- Detective Michael Bennett thriller, 2016)
Caught in the crossfire of a deadly standoff, Detective Michael Bennett must kill, or be killed. Tensions between America and Russia are the highest they've been since the Cold War. As the countries' two Presidents travel to the United Nations to iron out their differences, a fashionable husband and wife team of lethal special ops assassins prowls the streets of Manhattan hunting their prey, a law school professor hiding a scandalous secret.